PENGARUH ENVIRONMENTAL, SOCIAL AND GOVERNANCE (ESG), KUALITAS AUDIT, DAN KOMISARIS INDEPENDEN TERHADAP AGRESIVITAS PAJAK - Danica Vivian Lumbantobing; Cicely Delfina Harahap (STMIK Widuri Jakarta, 2025)
This study aims to analyze the effect of Environmental, Social, Governance (ESG), Audit Quality, and Independent Commissioners on tax aggressiveness in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The background of this research is based on the phenomenon of tax aggressiveness carried out by several large companies in Indonesia, such as PT Adaro Energy Tbk and PT Aneka Tambang Tbk, which has implications for significant losses to state revenue.The methodology used in this study is multiple regression analysis with secondary data in the form of financial reports and sustainability reports downloaded from the IDX website and the official websites of related companies. Sampels were selected using purposive sampling method based on certain criteria.The results showed that ESG has a significant effect on tax aggressiveness, which indicates that companies that are active in ESG activities tend to be more transparent and responsible in their tax payments. In contrast, audit quality and independent commissioners have no significant effect on tax aggressiveness. This shows that the presence of auditors from KAP Big 4 and the number of independent commissioners are not directly able to suppress tax avoidance by companies.